2022
DOI: 10.3390/molecules27175565
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Magnetic Carnation-like Hydroxyapatite/Basic Calcium Carbonate Nanocomposite and Its Adsorption Behaviors for Lead Ions in Water

Abstract: Calcium-enriched compounds have great potential in the treatment of heavy-metal contaminated wastewater. Preparing stable basic calcium carbonate (BCC), which is a calcium-enriched compound, and applying it in practice is a great challenge. This work investigated the formation process of hierarchical hydroxyapatite (HAP)/BCC nanocomposites and their adsorption behaviors regarding lead ions (Pb2+). The morphology of the HAP/BCC nanocomposite was controlled by the addition of monododecyl phosphate (MDP). The car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Given that P-CSH demonstrated a significantly greater adsorption capacity for Pb(II) compared to Cd(II) at initial concentrations of 800 mg/L for Pb(II) and 200 mg/L for Cd(II) ( Figure 6 ), no diffraction peaks associated with Cd(II) were observed in its adsorption product. Additionally, the presence of [CO 3 2− ] in these products could be attributed to CO 2 absorption from water or air during the adsorption or drying processes [ 50 , 51 ]. It was also observed that no diffraction peaks associated with C-S-H were detected in the products of Pb(II) adsorption alone or when both Pb(II) and Cd(II) were adsorbed simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Given that P-CSH demonstrated a significantly greater adsorption capacity for Pb(II) compared to Cd(II) at initial concentrations of 800 mg/L for Pb(II) and 200 mg/L for Cd(II) ( Figure 6 ), no diffraction peaks associated with Cd(II) were observed in its adsorption product. Additionally, the presence of [CO 3 2− ] in these products could be attributed to CO 2 absorption from water or air during the adsorption or drying processes [ 50 , 51 ]. It was also observed that no diffraction peaks associated with C-S-H were detected in the products of Pb(II) adsorption alone or when both Pb(II) and Cd(II) were adsorbed simultaneously.…”
Section: Resultsmentioning
confidence: 99%